Influence of low penetrance genes in susceptibility for breast cancer in the portuguese population of Beira Interior - Ramalhinho, Ana Cristina Monteiro (2016)
In Portugal, breast cancer presents the highest incidence and mortality rates among women diseases. Several genetic and non-genetic risk factors for the development of breast cancer have been identified, however, the molecular mechanisms related to breast carcinogenesis remain unclear. Less than 5% of all breast cancer cases are accounted for high-penetrance cancer susceptibility genes, so polymorphisms in low penetrance genes may be responsible for a relatively small, but frequent increase of cancer risk. The main objective of this thesis is to assess the influence of polymorphisms in low penetrating genes in breast cancer susceptibility, in a specific Portuguese population, the population of Beira Interior, in which this genetic effect was never accessed. The influence of polymorphic low penetrating genes of the estrogen biosynthetic pathway (CYP17A1 and CYP19A1), the estrogen metabolic pathway (CYP1B1, CYP1A1, COMT, GTSM1, GSTT1, GSTP1 and MTHFR), DNA damage signaling and repair pathway (TP53), and estrogenic response (ERα), in breast cancer susceptibility was analyzed. We found that deletion of GSTM1 and GSTT1, alone or in association, is associated with increased risk of breast cancer. Also, the homozygous or heterozygous presence of the variant allele in CYP19A1 codon 39 is significantly associated with an increased risk of breast cancer. The effects of this polymorphism in estradiol biosynthesis appear to be modulated by GSTM1 and GSTT1 deletion polymorphism in estrogen metabolic pathway, as breast cancer susceptibility was found to be lower in carriers of GSTM1 and GSTT1, independently of CYP19A1 genotype. Carriers of xx genotype in ERα gene, or simultaneous carriers of xx and pp genotypes, seemed to have a significant reduced risk of breast cancer. It was also found that TP53 variant allele in homozygosity or heterozygosity was associated with a significant increased risk for breast cancer. We also studied the prevalence of these polymorphisms in groups of women with different 5-year relative risk for developing breast cancer scores, calculated by the Modified Gail Model. We found that breast cancer risk score calculated by Gail Model was independent of the prevalence of risk genotypes, but the simultaneous presence of three, four and five risk genotypes was revealed to be more prevalent in breast cancer affected women than in unaffected women. As it was not found statistical association of risk genotypes with “high risk” or “low risk” scores calculated by Gail Model, it is demonstrated that, in this population, combinations of two or more polymorphisms in the low penetrating genes studied should be considered important risk factors for breast cancer development in an independent way of Gail Model. It is also aim of this thesis to present preliminary results on the use of dermal fibroblasts cultures as models of study of response to estrogens. Optimal conditions for culture of cells for in vitro assays with 17β-estradiol were established and fibroblasts responsiveness to estrogens was confirmed. Also, a method for isolation of human dermal fibroblasts was developed, what leaves open doors for future studies in this cell model. In summary, this thesis provides new data about the genetic profile of the female population of Beira Interior concerning breast cancer risk, and explores a new cell model to be used in molecular research in the field of the disease.